STUDENTS’ SELF-REGULATED LEARNING IN LEARNING WRITING - Ade Namira; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The aims of this study were to describe how the students implement their self-regulated learning in learning writing and to explain the reason why they do it as the way they do. A descriptive qualitative design was used in this study. The data and source of data were students’ activities of self-regulated learning in learning writing of Grade XII Culinary SMK Telkom 2 Medan. The data were collected by using questionnaire and interview. The data were analyzed by using descriptive qualitative. The results showed that (1) Most of the students did self-regulated learning activities with the level of frequency of use sometimes namely goal-setting (93%), environmental structuring (40%), self-evaluation (70.5%), task-strategies (40%), help-seeking (83.3%), and time management (50%). (2) The reasons why the students did self-regulated learning in learning writing as they do were: 1) Goal-setting (personal factor), 2) Environmental structuring (environmental factor), 3) Self-evaluation (behavior factor), 4) Task-strategies (personal factor), 5) Help-seeking (personal factor), and 6) Time management (personal factor).